A Multi-Stage Plasmodium vivax Malaria Vaccine Candidate Able to Induce Long-Lived Antibody Responses Against Blood Stage Parasites and Robust Transmission-Blocking Activity - McCaffery, Jessica N.; Fonseca, Jairo A.; Singh, Balwan; Cabrera-Mora, Monica; Bohannon, Caitlin; Jacob, Joshy; Arévalo-Herrera, Myriam; Moreno, Alberto (Frontiers in Cellular and Infection Microbiology, 2019)
Malaria control and interventions including long-lasting insecticide-treated nets, indoor residual spraying, and intermittent preventative treatment in pregnancy have resulted in a significant reduction in the number of Plasmodium falciparum cases. Considerable efforts have been devoted to P. falciparum vaccines development with much less to P. vivax. Transmission-blocking vaccines, which can elicit antibodies targeting Plasmodium antigens expressed during sexual stage development and interrupt transmission, offer an alternative strategy to achieve malaria control. The post-fertilization antigen P25 mediates several functions essential to ookinete survival but is poorly immunogenic in humans. Previous clinical trials targeting this antigen have suggested that conjugation to a carrier protein could improve the immunogenicity of P25. Here we report the production, and characterization of a vaccine candidate composed of a chimeric P. vivax Merozoite Surface Protein 1 (PvMSP1) genetically fused to P. vivax P25 (Pvs25) designed to enhance CD4+ T cell responses and assessed in a murine model. We demonstrate that antibodies elicited by immunization with this chimeric protein recognize both the erythrocytic and sexual stages and are able to block the transmission of P. vivax field isolates in standard membrane-feeding assays. These findings provide support for the continued development of multi-stage transmission blocking vaccines targeting the life-cycle stage responsible for clinical disease and the sexual-stage development accountable for disease transmission simultaneously.